Phase equilibria modelling constraints on P–T conditions during fluid catalysed conversion of granulite to eclogite in the Bergen Arcs, Norway. (20th December 2017) - Bhowany, K.; Hand, M.; Clark, C.; Kelsey, D. E.; Reddy, S. M.; Pearce, M. A.; Tucker, N. M.; Morrissey, L. J.
Abstract: Exhumed eclogitic crust is rare and exposures that preserve both protoliths and altered domains are limited around the world. Nominally anhydrous Neoproterozoic anorthositic granulites exposed on the island of Holsnøy, in the Bergen Arcs in western Norway, preserve different stages of progressive prograde deformation, together with the corresponding fluid‐assisted metamorphism, which record the conversion to eclogite during the Ordovician–Silurian Caledonian Orogeny. Four stages of deformation can be identified: (1) brittle deformation resulting in the formation of fractures and the generation of pseudotachylites in the granulite; (2) development of mesoscale shear zones associated with increased fluid–rock interaction; (3) the complete large‐scale replacement of granulite by hydrous eclogite with blocks of granulite sitting in an eclogitic "matrix"; and (4) the break‐up of completely eclogitized granulite by continued fluid influx, resulting in the formation of coarse‐grained phengite‐dominated mineral assemblages. P–T constraints derived from phase equilibria forward modelling of mineral assemblages of the early and later stages of the conversion to eclogite document burial and partial exhumation path with peak metamorphic conditions of 21–22 kbar and 670–690°C. The P–T models, in combination with existing T–t constraints, imply that the Lindås Nappe underwent extremely rapid retrogressive pressure change. Fluid infiltration began on the prograde burial path and continued throughout the recorded P–T evolution, implying a fluid source that underwent progressive dehydration during subduction of the granulites. However, in places limited fluid availability on the prograde path resulted in assemblages largely consuming the available fluid, essentially freezing in snapshots of the prograde evolution. These were carried metastably deeper into the mantle with strain and metamorphic recrystallization partitioned into areas where ongoing fluid infiltration was concentrated.